2020
DOI: 10.1124/dmd.120.090696
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Microsomes Immobilized on Magnetizable Beads: A Novel Approach to Study In Vitro Drug Metabolism

Abstract: Human liver microsomes (HLM) are a commonly used tool to study drug metabolism in vitro. Typical experiments conducted using suspensions of HLM can be challenging to separate from the incubation solution without lengthy ultracentrifugation steps. Magnetizable beads coated with silica (MGBS) were found to bind strongly to HLM, which could then be isolated and purified using a magnet. Binding of HLM to the MGBS (HLM-MGBS) was demonstrated to be mediated by strong interactions between microsomal phospholipids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Moreover, our studies show that the extent of compound adsorption to beads in the absence of HLM is negligible (data not shown). Furthermore, we previously showed that phospholipids can block HLM from binding to the beads, which indicates that it is possible to block the binding of material to the beads (Horspool et al, 2020). Thus, we hypothesized that the HLM would have the same effect of blocking other compounds from binding to the beads.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Moreover, our studies show that the extent of compound adsorption to beads in the absence of HLM is negligible (data not shown). Furthermore, we previously showed that phospholipids can block HLM from binding to the beads, which indicates that it is possible to block the binding of material to the beads (Horspool et al, 2020). Thus, we hypothesized that the HLM would have the same effect of blocking other compounds from binding to the beads.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, a 30 min incubation time was used to ensure that the binding of HLM to the beads reached equilibrium (Horspool et al, 2020). To optimize the time required for the binding, the time course of HLM binding to the beads was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations